2018
DOI: 10.1093/mnras/sty3094
|View full text |Cite
|
Sign up to set email alerts
|

Horndeski gravity without screening in binary pulsars

Abstract: We test the subclasses of Horndeski gravity without Vainshtein mechanism in the strong field regime of binary pulsars. We find the rate of energy losses via the gravitational radiation predicted by such theories and compare our results with observational data from quasi-circular binaries PSR J1738+0333, PSR J0737-3039, PSR J1012+5307. In addition, we consider few specific cases: the hybrid metric-Palatini f(R)-gravity and massive Brans-Dicke theory.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 93 publications
(136 reference statements)
1
34
0
Order By: Relevance
“…Therefore one should study gravitational scattering of the scalar field on matter degrees of freedom. The simplest suitable amplitude corresponds to the following diagram (11) Here we note matter degrees of freedom with a double plain line. We only consider tree-level interaction between the matter and gravity because of the two reasons.…”
Section: Anomalous Beyond Horndeski Couplingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore one should study gravitational scattering of the scalar field on matter degrees of freedom. The simplest suitable amplitude corresponds to the following diagram (11) Here we note matter degrees of freedom with a double plain line. We only consider tree-level interaction between the matter and gravity because of the two reasons.…”
Section: Anomalous Beyond Horndeski Couplingsmentioning
confidence: 99%
“…It must be noted that both Horndeski and beyond Horndeski models are well motivated and widely studied [5,6,7,8,9,10,11]. In particular, beyond Horndeski models originated from degenerate higher-order scalar-tensor (DHOST) theories [12,13,14,15,16,17,18,19] and it was shown that only models (3) have no ghost modes in the spectrum of tensor perturbations propagating about a cosmological background [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The system (11) was solved numerically and the corresponding plot for the critical impact parameter is presented in Fig. 3.…”
Section: Shadow Propertiesmentioning
confidence: 99%
“…3. System (11) has no solutions for certain configurations of metric parameters. In full analogy with the standard Reissner-Nordstrom metric, the absence of solution for (11) indicates the absence of the shadow.…”
Section: Shadow Propertiesmentioning
confidence: 99%
See 1 more Smart Citation